2019
DOI: 10.1002/art.40917
|View full text |Cite
|
Sign up to set email alerts
|

HLA Alleles Associated With Risk of Ankylosing Spondylitis and Rheumatoid Arthritis Influence the Gut Microbiome

Abstract: Objective HLA alleles affect susceptibility to more than 100 diseases, but the mechanisms that account for these genotype–disease associations are largely unknown. HLA alleles strongly influence predisposition to ankylosing spondylitis (AS) and rheumatoid arthritis (RA). Both AS and RA patients have discrete intestinal and fecal microbiome signatures. Whether these changes are the cause or consequence of the diseases themselves is unclear. To distinguish these possibilities, we examined the effect of HLA–B27 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(58 citation statements)
references
References 65 publications
2
56
0
Order By: Relevance
“…A data-driven study suggested that human gut microbial metabolites directly interact with 18.1% of all 166 RA-associated genes, participate in 71.4% of 311 RA-associated genetic pathways, and affect 51.3% ofRA-related phenotypes, including immune system pathways and phenotypes; this in turn demonstrated that the gut microbiota and its metabolites contribute to RA at genetic, functional, and phenotypic levels [55]. Another study reported that the HLA-B27 and HLA-DRB1 alleles affect susceptibility to RA, with effects on the gut microbiome that partially cause or increase the risk of RA [56]. In addition, changes in fecal bacteria may represent the RA condition or the outcome of RA progression.…”
Section: The Gut Microbiota and Autoimmune Diseasesmentioning
confidence: 99%
“…A data-driven study suggested that human gut microbial metabolites directly interact with 18.1% of all 166 RA-associated genes, participate in 71.4% of 311 RA-associated genetic pathways, and affect 51.3% ofRA-related phenotypes, including immune system pathways and phenotypes; this in turn demonstrated that the gut microbiota and its metabolites contribute to RA at genetic, functional, and phenotypic levels [55]. Another study reported that the HLA-B27 and HLA-DRB1 alleles affect susceptibility to RA, with effects on the gut microbiome that partially cause or increase the risk of RA [56]. In addition, changes in fecal bacteria may represent the RA condition or the outcome of RA progression.…”
Section: The Gut Microbiota and Autoimmune Diseasesmentioning
confidence: 99%
“…The studies focusing on the interaction between the metagenome and host genome in human complex diseases have become an interesting topic in the field of microbiome (Imhann et al, 2018;Asquith et al, 2019). Our study is the first to demonstrate the MWAS-GWAS interaction of the molecular pathways in the MS gut metagenome.…”
Section: Go Termmentioning
confidence: 65%
“…This in turn drives the Th1 response primarily by interferon gamma (IFNγ), and exacerbates gut inflammation ( 72 ). Another study focused on microbial dysbiosis associated with HLA alleles in healthy subjects with AS, and rheumatoid arthritis (RA), a chronic autoimmune disease defined by inflammation of the synovium and joint destruction ( 73 ). However, the authors did not observe HLA-B27-associated changes in Dialister in healthy subjects with either AS or RA associated alleles.…”
Section: Putative Pathobionts In Hla-b27 Associated Spondyloarthropatmentioning
confidence: 99%